Silver nanoprism-based plasmonic ELISA for sensitive detection of fluoroquinolones. Issue 16 (10th February 2020) - Yuan, Meifang; Xiong, Qirong; Zhang, Ganggang; Xiong, Zhijuan; Liu, Daofeng; Duan, Hongwei; Lai, Weihua
Abstract : Silver nanoprism-based plasmonic ELISA for qualitative and quantitative detection of fluoroquinolones. Abstract : Fluoroquinolones are synthetic antibiotics that are commonly used in animal husbandry, and the consumption of animal products with fluoroquinolone residues has imposed a serious threat to human health. Here, we report a plasmonic enzyme-linked immunosorbent assay (pELISA) method based on oxidative etching of silver nanoprisms (AgNPRs) for the quantitative and qualitative detection of danofloxacin (DAN), a fluoroquinolone antibiotic. AgNPRs that undergo colorimetric changes upon oxidative etching by H2 O2 serve as the signal transducer in our design. An indirect competitive pELISA was constructed by introducing biotinylated monoclonal antibody (mAb), streptavidin and biotinylated glucose oxidase, which catalyzes the generation of H2 O2 for etching AgNPRs. The quantitative detection limit of the proposed method was 0.24 ng mL −1 for DAN. The qualitative detection limit for DAN reached 0.32 ng mL −1, which was 32-fold lower than that of the assay using 3, 3′, 5, 5′-tetramethylbenzidine (TMB) as the signal transducer. The average recoveries of DAN in milk ranged from 103% to 121%, with a coefficient of variation of 0.6–3.41%. The recovery results were further confirmed using liquid chromatography-tandem mass spectrometry. In summary, the proposed AgNPR-etching pELISA exhibits high sensitivity, good accuracy and excellent reliability for the quantitative and qualitative detection of DAN in milk.